Letter - The Association of Civil Service Sorting Assistants, 6 May 1926 (page 2)
1926-05-06 "Letter - The Association of Civil Service Sorting Assistants, 6 May 1926 (page 2)" [g0585002.jpg], 6 May 1926, Association of Civil Service Sorting Assistants